2006
DOI: 10.1001/jama.295.12.1428
|View full text |Cite
|
Sign up to set email alerts
|

The Role of X Inactivation and Cellular Mosaicism in Women's Health and Sex-Specific Diseases

Abstract: Sex-specific manifestations of disease are most often attributed to differences in the reproductive apparatus or in life experiences. However, a good deal of sex differences in health issues have their origins in the genes on the sex chromosomes themselves and in X inactivation-the developmental program that equalizes their expression in males and females. Most females are mosaics, having a mixture of cells expressing either their mother's or father's X-linked genes. Often, cell mosaicism is advantageous, amel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
143
0
6

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(152 citation statements)
references
References 27 publications
3
143
0
6
Order By: Relevance
“…Female tissues are mosaic for most X-linked genes, resulting from Xi in every cell. Although inactivation of one X chromosome over the other is generally random, preferential inactivation of one chromosome (skewed Xi) can protect women against the consequences of X-linked gene mutations 104 . On the contrary the absence of Xi can have detrimental effects: for instance loss of Xist has been reported in breast, ovarian and cervical cancer cell lines 105,106 and, only in female mutant mice, it caused deregulation of hematopoietic lineages and emergence of myeloid neoplasms associated with genome wide changes in gene expression 107 .…”
Section: A) X Chromosomementioning
confidence: 99%
See 1 more Smart Citation
“…Female tissues are mosaic for most X-linked genes, resulting from Xi in every cell. Although inactivation of one X chromosome over the other is generally random, preferential inactivation of one chromosome (skewed Xi) can protect women against the consequences of X-linked gene mutations 104 . On the contrary the absence of Xi can have detrimental effects: for instance loss of Xist has been reported in breast, ovarian and cervical cancer cell lines 105,106 and, only in female mutant mice, it caused deregulation of hematopoietic lineages and emergence of myeloid neoplasms associated with genome wide changes in gene expression 107 .…”
Section: A) X Chromosomementioning
confidence: 99%
“…Sex hormones, especially estrogens, can play an important role in control of cellular senescence and aging-associated tissue deteriorations. Concomitantly, at the chromosomal level, it has been suggested that X-linked mutations are more likely to exert detrimental effects in male than female cells, which have the advantageous possibility of selective inactivation of the mutations-carrying X chromosome 104 .…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…A clinical study provided evidence for differences in the early cytokine response between females and males after injury, with males having persistently elevated IL-6 cytokine expression over time as compared to similarly injured females [56]. An alternative hypothesis states that Xlinked genetic differences between males and females, independent of hormonal status, responsible for these gender-based differential outcomes after injury in humans [56,57,58]. These studies suggest a new avenue for T/HS research and interaction with the field of endocrinology.…”
Section: Human Studies Of T/hsmentioning
confidence: 99%
“…Although relatively uncommon, there is also the possibility of metabolic interference when products from mutant cells interfere with the function of the normal cells. 50 The disorders discussed here result from severe elimination of gene function. It is likely that more subtle differences in the expression of these and other genes will produce more nuanced differences in how males and females manifest their mutations.…”
Section: Resultsmentioning
confidence: 99%